Separation axioms in neutrosophic supra topological space and neutrosophic supra bi-topological space - Riad K. Al-Hamido (Neutrosophic Sets and Systems, 2022)
In this paper, as a new separation axioms in neutrosophic supra topological space, NS-Ti- space (i=0,1,2) is built in this space. Moreover, SN.T1T2-open(closed) sets are defined in neutrosophic supra bi-topological spaces. Also SNBi-Ti-space (i=0,1,2) is built on this new neutrosophic sets. And their basic properties are presented. The relations between these new neutrosophic separation axioms is studied. Finally, many examples are presented.